TARGETED DELIVERY OF FACTORS AND CELLS FOR IMPROVING CARDIAC TISSUE REGENERATION AND HEART FUNCTION FOLLOWING MYOCARDIAL INFARCTION - Nurkesh, Ayan (Nazarbayev University School of Medicine, 2025)
Cardiovascular diseases (CVDs), including myocardial infarction (MI) and coronary artey disease, are the leading causes for global mortality. MI arises from the rupture of atherosclerotic plaques, triggering thrombosis, ischemia, and subsequent cardiomyocyte death. Heart has limitations to regenerate the tissue, fibrotic tissue replaces damaged myocardium, impairing cardiac function. While interventions like percutaneous coronary intervention reduce mortality, they do not regenerate tissue, underscoring the need for innovative therapies. Mesenchymal stem cells (MSCs) hold potential for cardiac repair, but their survival in ischemic environments remains suboptimal. Hydrogels, particularly chitosan-based cryogels, may enhance MSC retention and efficacy. This study investigates the combined delivery of MSCs and bioactive factors (IL-10, VEGF-A, FGF-2) via cryogels in a murine MI model. Results indicate reduced inflammation, enhanced angiogenesis, and improved cardiac regeneration, suggesting a novel strategy to mitigate post-MI fibrosis and advance cell- based therapies for CVDs.
Keywords: type of access: open access